Building and testing with Gradle - Berglund, Tim (O'Reilly, 2011)
Annotation
Online resource; title from title screen (Safari, viewed Dec. 5, 2011). - Print version record
Keywords: Computer software -- Development -- Management; Computer programming -- Management; Open source software; Gradle (Computer software); Logiciels libres; COMPUTERS; Software Development & Engineering; Quality Assurance & Testing; Computer programming; Management; Computer software; Development; Management; Java (Computer language); Application software; Design